UJI KESAHIHAN (VALIDITAS) PEMERIKSAAN D-DIMER CARA MENYARING KEKEBALAN (METODE IMUNOFILTRASI) DAN CARA MENGUKUR IMUNOTURBIDIMETRI - David Rustandi; Delita Prihatni; Tiene Rostini; Nina Tristina (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
D-Dimer parameter is the most usefull laboratory assay to detect the present of activated coagulation. The D-Dimer fragment directlyindicate the fibrinolitic proccess whereas the increasing mark of D-Dimer is the most hemostatic parameter that was used to detectthe early stage of Disseminated Intravascular Coagulation (DIC) and has a correlation with the patient prognosis. D-Dimer assay byimmunoturbidimetric method was used to detect antigen-antibody reaction automatically and it can detect D-Dimer concentration lessthan 0.5 μg/mL. The immunoturbidimetric method has a good correlation with the ELISA method, but the proccess is complicated, ishigh costed, and need the competence of practical human resource. D-Dimer assay with immunofiltration method has the same principleas immunoturbidimetric method, but it's work more simpler, low cost and does not need the competence of practical human resource.The aim of this study is to compare the D-Dimer assay concentration between immunofltration and immunoturbidimetric method. Therewere 30 plasma samples assayed with these two methods (immunoturbidimetric and immunofiltration), and then compared betweenthem. The samples were collected between November until December 2008 at Rumah Sakit dr. Hasan Sadikin Bandung. The validity ofD-Dimer using immunofiltration method showed sensitivity 74%, specificity 95%, predictive value of negative test (PV-) 22%, predictivevalue of positive test (PV+) 95% with likelihood ratio 5.2. The conclusion of this study so far that the immunofiltration method has agood validity for diagnosing. D-Dimer work rapidly with low cost laboratory assay than the immunoturbidimetric method.